2010
DOI: 10.1124/jpet.110.167965
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Doxorubicin-Induced Cardiomyopathy Using the Modified Anthracycline N-Benzyladriamycin-14-valerate (AD 198)

Abstract: The anthracycline doxorubicin (Dox) is an effective antitumor agent. However, its use is limited because of its toxicity in the heart. N- ) is a modified anthracycline with antitumor efficacy similar to that of Dox, but with significantly less cardiotoxicity and potentially cardioprotective elements. In the present study, we investigated the possibility of in vivo protective effects of low-dose AD 198 against Dox-induced cardiomyopathy. To do this, rats were divided into four groups: vehicle, Dox (20 mg/kg; si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…Doxorubicin has previously been found to reduce both left ventricular developed pressure and heart rate, also shown in this study [15,34,35]. Interestingly, the presented data show that doxorubicin treatment in the naïve hearts caused a drop in the heart rate readings as opposed to its effects in conditions of ischaemia and reperfusion injury where no significant decrease in the heart rate values were recorded.…”
Section: Discussionsupporting
confidence: 75%
“…Doxorubicin has previously been found to reduce both left ventricular developed pressure and heart rate, also shown in this study [15,34,35]. Interestingly, the presented data show that doxorubicin treatment in the naïve hearts caused a drop in the heart rate readings as opposed to its effects in conditions of ischaemia and reperfusion injury where no significant decrease in the heart rate values were recorded.…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, it activates PKC‐δ which is subjected to proteolysis by caspases‐3 involved in the promotion and intensification of the apoptotic signals with the aid of activation of p38 signalling pathway and fragmentation of PARP . In contrast to doxorubicin, compound 24 proved to be non‐cardiotoxic in rodent model through activation of the PKC‐ϵ pathway in cardiomyocytes …”
Section: Anthracyclinesmentioning
confidence: 99%
“…Nbenzyladriamycin-14-valerate (AD 198) is a newer lipophilic anthracycline, which is superior to doxorubicin (DOX) in murine cancer models and has novel biochemical pathways and pharmacological properties (He et al, 2005). It has been shown that the cells that had developed (multiple drug resistance) MDR toward DOX, were sensitive to AD 198 (Cai et al, 2010, Ganapathi et al, 1989. The cardiotoxicity manifested by DOX is also absent in AD 198 and that was one of the rationales for AD 198 development.…”
Section: Components Of Unilamellar Liposomal Drug Formulationsmentioning
confidence: 99%
“…AD 198 does not display the cardiotoxic property of doxorubicin. Moreover, it is cardioprotective to the cardiomyocytes from the damage caused by doxorubicin therapy (Cai et al, 2010). Previously it was known that the cardiotoxicity of doxorubicin is due to the generation of reactive oxygen species (ROS) from the semi-quinone ring.…”
Section: Ad 198 Mechanisms Of Actionmentioning
confidence: 99%